PERENCANAAN JALAN PADA SEGMEN INARI – BOFUWER (STA. 61 + 500 – 68 + 200) KABUPATEN KAIMANA PROVINSI PAPUA BARAT - Femmy Kindanti; Ibnu Sholichin (CI-TECH, 2021)
West Papua Province is a new province with a relatively low economic level due to inadequate road access. Many areas are isolated, which hampers the distribution of goods and services. One isolated area is the Kaimana Regency with Fakfak Regency. Therefore, to open regional isolation and improve the local community's economy, it is necessary to plan a road in the Inari – Bofuwer segment as an infrastructure that can connect the two areas.Road planning consists of geometric road planning based on Tata Cara Perencanaan Geometrik Jalan Antar Kota No. 38 Tahun 1997, road pavement thickness planning using the 2017 Bina Marga method, and road drainage planning based on Perencanaan Sistem Drainase Jalan Tahun 2006.The geometric design of the road for horizontal alignment obtained 13 Spiral-Circle-Spiral bends and 5 Spiral-Spiral bends. In contrast, the vertical alignment consists of 13 concave curves and 13 convex curves. The road pavement uses Burda or Burtu with a thickness of LPA Class A 250 mm, LPA Class B 110 mm, and a soil stabilization layer 150 mm. The planned road drainage channel is in the form of a trapezoid with a width of 0,4 – 0,6 meters and a height of 0,85 – 1,15 meters.